Efficient heat insulation type nano-pore polymer material for heat preservation bag and preparation method of efficient heat insulation type nano-pore polymer material
By preparing a polyamino modified composite nucleation agent to blend with polymer and using supercritical CO2 fluid to foam, the problem of poor insulation performance of existing nanopore polymer materials is solved, and high-efficiency thermal insulation nanopores are achieved The preparation of polymer materials significantly improves the insulation effect of the insulation bag.
Patent Information
- Application Number
- CN202411570685.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing nanopore polymer materials have poor thermal insulation performance, and there are limitations in preparation methods and performance optimization, making it difficult to meet the efficient insulation needs of insulation bags.
By preparing a polyamino-modified composite nucleation agent and blending it with the polymer, physical foaming is carried out using supercritical CO2 fluid to form a highly efficient thermally insulated nanopore polymer material.
The thermal insulation performance of nanopore polymer materials is significantly improved, the insulation effect of insulation bags is enhanced, and the process optimization reduces costs and improves the industrial economic effect.
Smart Images

Figure BDA0005120369790000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, and in particular to a high-efficiency thermal insulation nanoporous polymer material for thermal insulation bags and a preparation method thereof. Background Art
[0002] In today's society, the demand for thermal insulation bags is increasing, especially in the fields of food, beverages, medical treatment, etc. Efficient thermal insulation performance is essential to maintain the temperature of the package contents, which can effectively reduce energy loss, extend the shelf life of food, and improve the user experience.
[0003] Existing insulation materials mainly include foam plastics, silicone and metal films. Although they have certain insulation properties, they are insufficient in terms of lightness, flexibility and cost control, and there is an urgent need for the development of alternative materials. Nanoporous polymer materials have shown great potential in the regulation mechanism of gas and heat energy transmission due to their unique pore structure, and have therefore become a research hotspot. This type of material can effectively slow down the heat transfer from the external environment to the internal material and improve the insulation effect of the insulation bag.
[0004] However, the thermal insulation performance of nanoporous polymer materials in the prior art is poor, and there are still certain limitations in the preparation method and performance optimization, which requires further technical improvements. Therefore, the development of an efficient thermal insulation nanoporous polymer material for thermal insulation bags and its preparation method is of great significance for improving the performance of thermal insulation bags. Summary of the invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a high-efficiency insulating nanoporous polymer material for insulation bags and a preparation method thereof, which solves the problem that the existing nanoporous polymer materials have poor thermal insulation performance, certain limitations in preparation methods and performance optimization, and require further technical improvements.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag comprises the following components in parts by weight:
[0008] 1 part of polyamino modified composite nucleating agent, 20-50 parts of polymer;
[0009] Wherein, the polyamino modified composite nucleating agent is prepared by the following steps:
[0010] Step 1: Add graphite powder, concentrated sulfuric acid and concentrated nitric acid to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 5-10 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then add potassium permanganate and continue stirring and reacting for 10-15 hours at a temperature of 50-55°C, then continue stirring and reacting for 1-2 hours at a temperature of 90-100°C, and after the reaction is completed, pour the reaction product into distilled water, then add hydrogen peroxide solution, then stand for 2-3 hours, then centrifuge, wash the precipitate with hydrochloric acid solution and distilled water for 3-5 times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 2-3 hours to obtain graphene oxide;
[0011] Step 2: Add Zn(NO3)2·6H2O, 1,4-benzenedicarboxylic acid and N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add graphene oxide and continue to stir and react for 1-2 hours, then place in a vacuum drying oven, dry for 70-75 hours at a temperature of 60-65°C, then add hexadecyltrimethylammonium bromide and continue to dry for 1-2 hours at a temperature of 100-110°C, after the reaction is completed, cool the reaction product to room temperature, then add triethanolamine and stir and react for 10-15 minutes, then centrifuge, wash the precipitate with chloroform 2-3 times, then soak it in chloroform for 8-12 hours, then place it in a vacuum drying oven, and dry it for 4-5 hours at a temperature of 50-55°C to obtain a composite nucleating agent;
[0012] Step 3: Add the composite nucleating agent, epichlorohydrin and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 55-60°C and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 2-3 times, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 4-5 hours to obtain an epoxy-modified composite nucleating agent;
[0013] Step 4: Add the epoxy-modified composite nucleating agent, polyethyleneimine and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 55-60°C and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, wash the precipitate with distilled water 2-3 times, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 6-8 hours to obtain a polyamino-modified composite nucleating agent;
[0014] Wherein, the polymer is polymethyl methacrylate.
[0015] As a further solution of the present invention: the usage ratio of the graphite powder, concentrated sulfuric acid, concentrated nitric acid, potassium permanganate and hydrogen peroxide solution in step 1 is 1g:96-108mL:12-15mL:6-8g:4-5mL.
[0016] As a further solution of the present invention: in step 1, the mass fraction of the concentrated sulfuric acid is 98%, the mass fraction of the concentrated nitric acid is 68%, the mass fraction of the hydrogen peroxide solution is 30%, and the mass fraction of the hydrochloric acid solution is 5%.
[0017] As a further scheme of the present invention: the usage ratio of Zn(NO3)2·6H2O, 1,4-benzenedicarboxylic acid, N,N-dimethylformamide, graphene oxide, hexadecyltrimethylammonium bromide and triethanolamine in step 2 is 6mmol:2mmol:30-50mL:0.04-0.06g:2mmol:2mmol.
[0018] As a further solution of the present invention: the usage ratio of the composite nucleating agent, epichlorohydrin and deionized water in step three is 1g:4-5mL:60-70mL.
[0019] As a further solution of the present invention: the usage ratio of the epoxy-modified composite nucleating agent, polyethyleneimine and deionized water in step 4 is 1 g: 0.5-1.5 mL: 50-55 mL.
[0020] As a further solution of the present invention: the polyethyleneimine in step 4 is polyethyleneimine with Mw=600.
[0021] As a further solution of the present invention: a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag comprises the following steps:
[0022] Step s1: weigh 1 part of a polyamino-modified composite nucleating agent and 20-50 parts of a polymer according to weight, and set aside;
[0023] Step s2: adding the polyamino-modified composite nucleating agent and the polymer into a twin-screw extruder, mixing at a temperature of 170-190° C. for 5-10 minutes, and then melt-extruding into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 170-190° C. and a pressure of 5-6 MPa for 10 minutes to obtain a composite material sheet;
[0024] Step s3: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 3-5 hours at a temperature of 25-30°C and a pressure of 4-6Mpa, then quickly release the pressure to 1Mpa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 80-100°C for foaming for 30-40 seconds, and then quench it in an ice bath for 2-3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0025] Beneficial effects of the present invention:
[0026] The invention discloses a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag and a preparation method thereof. The invention firstly uses graphite powder as a raw material to prepare graphene oxide, then uses Zn(NO3)2·6H2O and 1,4-benzenedicarboxylic acid as raw materials to prepare a metal organic framework, and loads graphene oxide on the metal organic framework to obtain a composite nucleating agent. Then, the composite nucleating agent is treated with epichlorohydrin, and a large number of epoxy groups are grafted on the particle surface of the composite nucleating agent after the ring-opening and ring-closing reaction of epichlorohydrin to obtain an epoxy-modified composite nucleating agent. The nucleating agent is synthesized, and then the epoxy-modified composite nucleating agent is treated with polyethyleneimine, and the epoxy groups on the epoxy-modified composite nucleating agent react with the amino groups on the polyethyleneimine, thereby grafting a large number of amino groups and imino groups on the particle surface of the composite nucleating agent to obtain a polyamino-modified composite nucleating agent, and finally the polyamino-modified composite nucleating agent and the polymer are blended, and then physically foamed with supercritical CO2 fluid to obtain a highly efficient insulating nanoporous polymer material for thermal insulation bags; metal organic framework is a kind of metal and organic The three-dimensional porous skeleton material formed by the organic ligands connected by chemical bonds, hydrogen bonds or van der Waals forces has a high specific surface area and porosity, so it can provide more nucleation sites, so that nucleation occurs in nanocavities with lower energy, so that more supercritical CO2 fluid can be absorbed for physical foaming, thereby increasing the density of the pores. After doping graphene oxide therein, the graphene oxide has a single-layer hexagonal honeycomb structure and contains boundary groups and planar defects. This structure gives graphene a large specific surface area, provides abundant sites for the adsorption of gas molecules, and makes the two show a synergistic effect in gas adsorption. After a large number of amino and imino groups are grafted, due to the affinity of CO2 with amino and imino functional groups, the adsorption of supercritical CO2 fluid is further realized, and finally the efficient and large-scale absorption of supercritical CO2 fluid is realized, the density of the pores is further increased, the purpose of thermal insulation is achieved, and the insulation bag is given excellent thermal insulation performance, which is helpful to promote the development of high-performance insulation bags and improve the economic effect of the industry. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] This embodiment is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0030] Step S1: 1g of graphite powder, 96mL of concentrated sulfuric acid with a mass fraction of 98% and 12mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of -5°C and a stirring rate of 300r / min for 5min, then 6g of potassium permanganate is added and the stirring reaction is continued for 10h under the condition of heating to 50°C, and then the stirring reaction is continued for 1h under the condition of heating to 90°C. After the reaction is completed, the reaction product is poured into distilled water, and then 4mL of hydrogen peroxide solution with a mass fraction of 30% is added, and then it is allowed to stand for 2h, and then centrifuged, and the precipitate is washed 3 times with a hydrochloric acid solution with a mass fraction and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 50°C for 2h to obtain graphene oxide;
[0031] Step S2: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 30 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for 20 min at a temperature of 25°C and a stirring rate of 300 r / min, then 0.04 g of graphene oxide was added and the stirring reaction was continued for 1 h, then the mixture was placed in a vacuum drying oven and dried at a temperature of 60°C for 70 h, then 2 mmol hexadecyltrimethylammonium bromide was added and the temperature was raised to 100°C and the mixture was continued to be dried for 1 h, after the reaction was completed, the reaction product was cooled to room temperature, then 2 mmol triethanolamine was added and stirred for 10 min, then centrifuged, the precipitate was washed twice with chloroform, then immersed in chloroform for 8 h, then placed in a vacuum drying oven, and dried at a temperature of 50°C for 4 h to obtain a composite nucleating agent;
[0032] Step S3: 1 g of a composite nucleating agent, 4 mL of epichlorohydrin and 60 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 55° C. and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at 50° C. for 4 h to obtain an epoxy-modified composite nucleating agent;
[0033] Step S4: 1 g of epoxy-modified composite nucleating agent, 0.5 mL of polyethyleneimine with a weight of 600, and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 55° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 6 h to obtain a polyamino-modified composite nucleating agent;
[0034] Step S5: weighing 1 part of a polyamino-modified composite nucleating agent and 50 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0035] Step S6: adding the polyamino-modified composite nucleating agent and the polymer into a twin-screw extruder, mixing them at a temperature of 170° C. for 5 minutes, and then melt-extruding them into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 170° C. and a pressure of 5 MPa for 10 minutes to obtain a composite material sheet;
[0036] Step S7: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 3 hours at a temperature of 25°C and a pressure of 4 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 80°C for foaming for 30 seconds, and then quench it in an ice bath for 2 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0037] Embodiment 2:
[0038] This embodiment is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0039] Step S1: 1g of graphite powder, 102mL of concentrated sulfuric acid with a mass fraction of 98% and 14mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of -3°C and a stirring rate of 350r / min for 8min, then 7g of potassium permanganate is added and the stirring reaction is continued for 12h under the condition of heating to 52°C, and then the stirring reaction is continued for 1.5h under the condition of heating to 95°C. After the reaction is completed, the reaction product is poured into distilled water, and then 4.5mL of hydrogen peroxide solution with a mass fraction of 30% is added, and then it is allowed to stand for 2.5h, and then centrifuged. The precipitate is washed 4 times with a mass fraction of 5% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 52°C for 2.5h to obtain graphene oxide;
[0040] Step S2: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 40 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28°C and a stirring rate of 350 r / min for 25 min, then 0.05 g graphene oxide was added and the stirring reaction was continued for 1.5 h, then the mixture was placed in a vacuum drying oven and dried at a temperature of 62°C for 72 h, then 2 mmol hexadecyltrimethylammonium bromide was added and the temperature was raised to 105°C and the mixture was continued to be dried for 1.5 h, after the reaction was completed, the reaction product was cooled to room temperature, then 2 mmol triethanolamine was added and stirred for reaction for 12 min, then centrifuged, the precipitate was washed twice with chloroform, then immersed in chloroform for 10 h, then placed in a vacuum drying oven, and dried at a temperature of 52°C for 4.5 h to obtain a composite nucleating agent;
[0041] Step S3: 1 g of a composite nucleating agent, 4.5 mL of epichlorohydrin and 65 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 58° C. and stirred for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at 52° C. for 4.5 h to obtain an epoxy-modified composite nucleating agent;
[0042] Step S4: 1 g of epoxy-modified composite nucleating agent, 1 mL of polyethyleneimine with a weight of 600, and 52 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then heated to 58° C. and continued to stir for reaction for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 7 h to obtain a polyamino-modified composite nucleating agent;
[0043] Step S5: weighing 1 part of a polyamino-modified composite nucleating agent and 35 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0044] Step S6: adding the polyamino-modified composite nucleating agent and the polymer into a twin-screw extruder, mixing at a temperature of 180° C. for 8 minutes, and then melt-extruding into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 180° C. and a pressure of 5.5 MPa for 10 minutes to obtain a composite material sheet;
[0045] Step S7: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 4 hours at a temperature of 28°C and a pressure of 5 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 90°C for foaming for 35 seconds, and then quench it in an ice bath for 2.5 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0046] Embodiment 3:
[0047] This embodiment is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0048] Step S1: 1g of graphite powder, 108mL of concentrated sulfuric acid with a mass fraction of 98% and 15mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 0°C and a stirring rate of 400r / min for 10min, then 8g of potassium permanganate is added and the stirring reaction is continued for 15h under the condition of heating to 55°C, and then the stirring reaction is continued for 2h under the condition of heating to 100°C. After the reaction is completed, the reaction product is poured into distilled water, and then 5mL of a 30% hydrogen peroxide solution is added, and then it is allowed to stand for 3h, and then centrifuged. The precipitate is washed 5 times with a 5% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 3h to obtain graphene oxide;
[0049] Step S2: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 50 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 30 min, then 0.06 g of graphene oxide was added and stirred for reaction for 2 h, then placed in a vacuum drying oven and dried at a temperature of 65°C for 75 h, then 2 mmol hexadecyltrimethylammonium bromide was added and the temperature was raised to 110°C and continued to dry for 2 h, after the reaction was completed, the reaction product was cooled to room temperature, then 2 mmol triethanolamine was added and stirred for reaction for 15 min, then centrifuged, the precipitate was washed with chloroform 3 times, then immersed in chloroform for 12 h, then placed in a vacuum drying oven, and dried at a temperature of 55°C for 5 h to obtain a composite nucleating agent;
[0050] Step S3: 1 g of a composite nucleating agent, 5 mL of epichlorohydrin and 70 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at 55° C. for 5 h to obtain an epoxy-modified composite nucleating agent;
[0051] Step S4: 1 g of epoxy-modified composite nucleating agent, 1.5 mL of polyethyleneimine with a molecular weight of 600, and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 60° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at 55° C. for 8 h to obtain a polyamino-modified composite nucleating agent;
[0052] Step S5: weighing 1 part of a polyamino-modified composite nucleating agent and 20 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0053] Step S6: adding the polyamino-modified composite nucleating agent and the polymer into a twin-screw extruder, mixing them at a temperature of 190° C. for 10 minutes, and then melt-extruding them into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 190° C. and a pressure of 6 MPa for 10 minutes to obtain a composite material sheet;
[0054] Step S7: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 5 hours at a temperature of 30°C and a pressure of 6 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 100°C for foaming for 40 seconds, and then quench it in an ice bath for 3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0055] Comparative Example 1:
[0056] This comparative example is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0057] Step S1: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 50 mL N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer and a thermometer, stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 30 minutes, then placed in a vacuum drying oven, dried at a temperature of 65°C for 75 hours, then added with 2 mmol hexadecyltrimethylammonium bromide and continued to dry for 2 hours at a temperature of 110°C, after the reaction is completed, the reaction product is cooled to room temperature, then added with 2 mmol triethanolamine, stirred for reaction for 15 minutes, then centrifuged, the precipitate is washed with chloroform 3 times, then immersed in chloroform for 12 hours, then placed in a vacuum drying oven, dried at a temperature of 55°C for 5 hours, and a nucleating agent is obtained;
[0058] Step S2: weighing 1 part of a nucleating agent and 20 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0059] Step S3: adding a nucleating agent and a polymer into a twin-screw extruder, mixing at a temperature of 190° C. for 10 minutes, and then melt-extruding into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 190° C. and a pressure of 6 MPa for 10 minutes to obtain a composite material sheet;
[0060] Step S4: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 5 hours at a temperature of 30°C and a pressure of 6 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 100°C for foaming for 40 seconds, and then quench it in an ice bath for 3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0061] Comparative Example 2:
[0062] This comparative example is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0063] Step S1: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 50 mL N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer and a thermometer, stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 30 minutes, then placed in a vacuum drying oven, dried at a temperature of 65°C for 75 hours, then added with 2 mmol hexadecyltrimethylammonium bromide and continued to dry for 2 hours at a temperature of 110°C, after the reaction is completed, the reaction product is cooled to room temperature, then added with 2 mmol triethanolamine, stirred for reaction for 15 minutes, then centrifuged, the precipitate is washed with chloroform 3 times, then immersed in chloroform for 12 hours, then placed in a vacuum drying oven, dried at a temperature of 55°C for 5 hours, and a nucleating agent is obtained;
[0064] Step S2: 1 g of nucleating agent, 5 mL of epichlorohydrin and 70 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at 55° C. for 5 h to obtain an epoxy-modified nucleating agent;
[0065] Step S3: 1 g of epoxy modified nucleating agent, 1.5 mL of polyethyleneimine with LMW=600 and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then heated to 60° C. and continued to stir for reaction for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 8 h to obtain a polyamino modified nucleating agent;
[0066] Step S4: weighing 1 part of a polyamino-modified nucleating agent and 20 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0067] Step S5: adding the polyamino modified nucleating agent and the polymer into a twin-screw extruder, mixing them at a temperature of 190° C. for 10 minutes, and then melt-extruding them into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 190° C. and a pressure of 6 MPa for 10 minutes to obtain a composite material sheet;
[0068] Step S6: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 5 hours at a temperature of 30°C and a pressure of 6 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 100°C for foaming for 40 seconds, and then quench it in an ice bath for 3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0069] Comparative Example 3:
[0070] This comparative example is a method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, comprising the following steps:
[0071] Step S1: 1g of graphite powder, 108mL of concentrated sulfuric acid with a mass fraction of 98% and 15mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 0°C and a stirring rate of 400r / min for 10min, then 8g of potassium permanganate is added and the stirring reaction is continued for 15h under the condition of heating to 55°C, and then the stirring reaction is continued for 2h under the condition of heating to 100°C. After the reaction is completed, the reaction product is poured into distilled water, and then 5mL of a 30% hydrogen peroxide solution is added, and then it is allowed to stand for 3h, and then centrifuged. The precipitate is washed 5 times with a 5% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 3h to obtain graphene oxide;
[0072] Step S2: 6 mmol Zn(NO3)2·6H2O, 2 mmol 1,4-benzenedicarboxylic acid and 50 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 30 min, then 0.06 g of graphene oxide was added and stirred for reaction for 2 h, then placed in a vacuum drying oven and dried at a temperature of 65°C for 75 h, then 2 mmol hexadecyltrimethylammonium bromide was added and the temperature was raised to 110°C and continued to dry for 2 h, after the reaction was completed, the reaction product was cooled to room temperature, then 2 mmol triethanolamine was added and stirred for reaction for 15 min, then centrifuged, the precipitate was washed with chloroform 3 times, then immersed in chloroform for 12 h, then placed in a vacuum drying oven, and dried at a temperature of 55°C for 5 h to obtain a composite nucleating agent;
[0073] Step S3: weighing 1 part of a composite nucleating agent and 20 parts of a polymer according to weight for later use; wherein the polymer is polymethyl methacrylate;
[0074] Step S4: adding the composite nucleating agent and the polymer into a twin-screw extruder, mixing them at a temperature of 190° C. for 10 minutes, and then melt-extruded into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 190° C. and a pressure of 6 MPa for 10 minutes to obtain a composite material sheet;
[0075] Step S5: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 5 hours at a temperature of 30°C and a pressure of 6 MPa, then quickly release the pressure to 1 MPa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 100°C for foaming for 40 seconds, and then quench it in an ice bath for 3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.
[0076] The performance of the highly efficient heat-insulating nanoporous polymer materials for thermal insulation bags of Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in the following table:
[0077]
[0078] Referring to the data in the above table, it can be seen that the nanoporous polymer material of the present application has excellent thermal insulation performance.
[0079] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0080] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, characterized in that: It comprises the following components in parts by weight: 1 part of polyamino modified composite nucleating agent, 20-50 parts of polymer; Wherein, the polyamino modified composite nucleating agent is prepared by the following steps: Step 1: Add graphite powder, concentrated sulfuric acid and concentrated nitric acid to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 5-10 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then add potassium permanganate and continue stirring and reacting for 10-15 hours at a temperature of 50-55°C, then continue stirring and reacting for 1-2 hours at a temperature of 90-100°C, and after the reaction is completed, pour the reaction product into distilled water, then add hydrogen peroxide solution, then stand for 2-3 hours, then centrifuge, wash the precipitate with hydrochloric acid solution and distilled water for 3-5 times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 2-3 hours to obtain graphene oxide; Step 2: Add Zn(NO3)2·6H2O, 1,4-benzenedicarboxylic acid and N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add graphene oxide and continue to stir and react for 1-2 hours, then place in a vacuum drying oven, dry for 70-75 hours at a temperature of 60-65°C, then add hexadecyltrimethylammonium bromide and continue to dry for 1-2 hours at a temperature of 100-110°C, after the reaction is completed, cool the reaction product to room temperature, then add triethanolamine and stir and react for 10-15 minutes, then centrifuge, wash the precipitate with chloroform 2-3 times, then soak it in chloroform for 8-12 hours, then place it in a vacuum drying oven, and dry it for 4-5 hours at a temperature of 50-55°C to obtain a composite nucleating agent; Step 3: Add the composite nucleating agent, epichlorohydrin and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 55-60°C and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 2-3 times, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 4-5 hours to obtain an epoxy-modified composite nucleating agent; Step 4: Add the epoxy-modified composite nucleating agent, polyethyleneimine and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 55-60°C and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, wash the precipitate with distilled water 2-3 times, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 6-8 hours to obtain a polyamino-modified composite nucleating agent; Wherein, the polymer is polymethyl methacrylate.
2. The highly efficient heat-insulating nanoporous polymer material for thermal insulation bags according to claim 1, characterized in that: The usage ratio of the graphite powder, concentrated sulfuric acid, concentrated nitric acid, potassium permanganate and hydrogen peroxide solution in step 1 is 1g:96-108mL:12-15mL:6-8g:4-5mL.
3. The highly efficient heat-insulating nanoporous polymer material for heat-insulating bags according to claim 1, characterized in that: The mass fraction of the concentrated sulfuric acid in step 1 is 98%, the mass fraction of the concentrated nitric acid is 68%, the mass fraction of the hydrogen peroxide solution is 30%, and the mass fraction of the hydrochloric acid solution is 5%.
4. The highly efficient heat-insulating nanoporous polymer material for thermal insulation bags according to claim 1, characterized in that: The dosage ratio of the Zn(NO3)2·6H2O, 1,4-benzenedicarboxylic acid, N,N-dimethylformamide, graphene oxide, hexadecyltrimethylammonium bromide and triethanolamine in step 2 is 6mmol:2mmol:30-50mL:0.04-0.06g:2mmol:2mmol.
5. The highly efficient heat-insulating nanoporous polymer material for heat-insulating bags according to claim 1, characterized in that: The usage ratio of the composite nucleating agent, epichlorohydrin and deionized water in step three is 1g:4-5mL:60-70mL.
6. The highly efficient heat-insulating nanoporous polymer material for heat-insulating bags according to claim 1, characterized in that: The usage ratio of the epoxy-modified composite nucleating agent, polyethyleneimine and deionized water in step 4 is 1 g: 0.5-1.5 mL: 50-55 mL.
7. The highly efficient heat-insulating nanoporous polymer material for thermal insulation bags according to claim 1, characterized in that: The polyethyleneimine in step 4 is polyethyleneimine with Mw=600.
8. A method for preparing a highly efficient heat-insulating nanoporous polymer material for a heat-insulating bag, characterized in that: The following steps are involved: Step s1: weigh 1 part of a polyamino-modified composite nucleating agent and 20-50 parts of a polymer according to weight, and set aside; Step s2: adding the polyamino-modified composite nucleating agent and the polymer into a twin-screw extruder, mixing at a temperature of 170-190° C. for 5-10 minutes, and then melt-extruding into a circular open mold with a thickness of 1 mm and a radius of 1 cm, and then maintaining the pressure at a temperature of 170-190° C. and a pressure of 5-6 MPa for 10 minutes to obtain a composite material sheet; Step s3: Place the composite material sheet in a CO2 high-pressure reactor, exhaust the air, then introduce supercritical carbon dioxide and react for 3-5 hours at a temperature of 25-30°C and a pressure of 4-6Mpa, then quickly release the pressure to 1Mpa within 1 second, then cool the reaction product to room temperature, then soak it in a constant temperature water bath at 80-100°C for foaming for 30-40 seconds, and then quench it in an ice bath for 2-3 minutes to obtain a high-efficiency insulating nanoporous polymer material for insulation bags.